TECHNIQUE OF VIBRATION MONITORING - Chichkov, Boris A. (Nauchnyĭ vestnik MGTU GA (Online), 2018)
Vibration monitoring of machines is an integral part of their technical health estimation while in service and  prevention of collapse resulting from resonance conditions operation or material fatigue.Aviation gas-turbine engines and land based gas turbine – typical representatives of the of machines which are subject obligatory vibro-monitoring. In most cases it should be carried out continuously, but, in some cases (for example, power-plants of light helicopters), vibro-monitoring is performed within periods reckoned in dozens of hours. Now one-axial vibration transmitters of various types are thus used. Anyway, the data received as a result of vibro-monitoring are processed, first of all, with the use of range verification and a number of  smoothing modes and the estimation of a tendency of vibration change modes while in service, examples of which shown on the engines are displayed in a paper. In some cases, there is a necessity of the simplified estimation of a vibrational condition of the machine for additional points or holding operative primary vibro-monitoring without engaging of a rented control equipment. The possible solution is the use of the modern mobile devices equipped with acceleration transmitters and the specialized software for archiving and vibro-monitoring data presentation in real-time mode. In the training process these devices appear full-scale substitution of vibration pickups and an oscillograph sheaf at estimating critical frequencies of rotors rotation with the possibility of archiving of the monitored data for the further processing.The vibrational monitoring technique with the use of microelectromechanical systems of modern mobile devices, has a number of advantages over the other ways. Particularly, the simultaneous three-axial estimation of vibration acceleration and a vibration vector with the graphic and character data presentation in real-time mode and more archiving and operative data processing opportunities, is executed.